2007
DOI: 10.3748/wjg.v13.i44.5888
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in colorectal cancer: The first step for individualized-therapy

Abstract: Interindividual differences in the toxicity and response to anticancer therapies are currently observed in practically all available treatment regimens. A goal of cancer therapy is to predict patient response and toxicity to drugs in order to facilitate the individualization of patient treatment. Identification of subgroups of patients that differ in their prognosis and response to treatment could help to identify the best available drug therapy according the genetic profile. Several mechanisms have been sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…These initial experiments have been reproduced in additional cell types including colon cancer derived cell lines (data not shown). Additional evidence has been reported that indicates a clear inhibition of the PI3K/AKT and ERK signaling pathways by ChoK inhibitors [38], [39], [40]. However, in the cellar systems used in this study, neither MAPK nor AKT signaling or ceramides generation are significantly altered by 5-FU treatment alone.…”
Section: Discussionsupporting
confidence: 51%
“…These initial experiments have been reproduced in additional cell types including colon cancer derived cell lines (data not shown). Additional evidence has been reported that indicates a clear inhibition of the PI3K/AKT and ERK signaling pathways by ChoK inhibitors [38], [39], [40]. However, in the cellar systems used in this study, neither MAPK nor AKT signaling or ceramides generation are significantly altered by 5-FU treatment alone.…”
Section: Discussionsupporting
confidence: 51%
“…This area of research has been comprehensively reviewed recently by Asghar et al [56], Bandrés et al [57], Benheim et al [58], Coate et al [59], De Roock et al [60], and Ross et al [61] and forms the basis of the rich pharmacogenetic resource, PharmGKB® (http://www.pharmgkb.org) which documents each therapeutic agent together with an aggregated list of SNPs reported in the literature to be associated with treatment outcome.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…In the former group, a polymorphism in the X-ray repair cross-complementing group 1 enzyme (XRCC1) -which is part of the base excision repair system -has been associated with variable initiation of DNA repair. [57] In addition, a polymorphism in a component of the ubiquitous nucleotide excision repair pathway -the excision repair cross complementing group 2 (ERCC2) gene -has been significantly associated with a clinical response to platinum-based chemotherapy. [57] However, there are no known polymorphisms in the DNA mismatch repair pathway associated with variation in treatment response with Oxaliplatin.…”
Section: Markers Of Treatment Outcomes When Treated With Classical Chmentioning
confidence: 99%
See 1 more Smart Citation
“…2.7 Potential role of microRNAs in modulating anticancer drug and radiation response Drug resistance and the comparative impact of radiation has been fairly frequently studied in cancer cells in vitro (Bandres, 2007;DiGennaro, 2009). However, our knowledge of the molecular events that take place in response to anticancer drugs and radiation in human tumours in vivo is very limited, and this is even more true of microRNA expression changes induced by these events.…”
mentioning
confidence: 99%